2021
DOI: 10.3389/fncel.2021.617308
|View full text |Cite
|
Sign up to set email alerts
|

Brain Metabolite, N-Acetylaspartate Is a Potent Protein Aggregation Inhibitor

Abstract: Deposition of toxic protein inclusions is a common hallmark of many neurodegenerative disorders including Alzheimer's disease, Parkinson disease etc. N-acetylaspartate (NAA) is an important brain metabolite whose levels got altered under various neurodegenerative conditions. Indeed, NAA has been a widely accepted biological marker for various neurological disorders. We have also reported that NAA is a protein stabilizer. In the present communication, we investigated the role of NAA in modulating the aggregatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 45 publications
0
5
0
Order By: Relevance
“…Another example of sorter-dependent change was the higher depletion of N-acetyl aspartic acid (NAA) in droplet-based sorted cells. This could make them more prone to endoplasmic reticulum (ER) stress since NAA sustains the intracellular UDP-N-acetylglucosamine levels, enabling protein synthesis under low glucose conditions, which in turn suppresses endoplasmic reticulum (ER) stress. , Similarly, several tryptophan metabolism intermediates showed larger changes when sorted with a droplet-based sorter, which are known for their role as antioxidant and ROS scavengers, indicating exposure to oxidative stress . Other metabolites such as nicotinamide, folate, and riboflavin, involved in protecting the cell membrane, proteins, and DNA from oxidative damage, were also significantly reduced in droplet-based cell sorting. In agreement with Binek et al, droplet-based sorting decreased diacylglycerol (DG) family members, which might be due to mechanical stress, electrostatic potential, or elastic stress dependent phospholipase C or DG lipase activity on lipid membranes (Figure S2f).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Another example of sorter-dependent change was the higher depletion of N-acetyl aspartic acid (NAA) in droplet-based sorted cells. This could make them more prone to endoplasmic reticulum (ER) stress since NAA sustains the intracellular UDP-N-acetylglucosamine levels, enabling protein synthesis under low glucose conditions, which in turn suppresses endoplasmic reticulum (ER) stress. , Similarly, several tryptophan metabolism intermediates showed larger changes when sorted with a droplet-based sorter, which are known for their role as antioxidant and ROS scavengers, indicating exposure to oxidative stress . Other metabolites such as nicotinamide, folate, and riboflavin, involved in protecting the cell membrane, proteins, and DNA from oxidative damage, were also significantly reduced in droplet-based cell sorting. In agreement with Binek et al, droplet-based sorting decreased diacylglycerol (DG) family members, which might be due to mechanical stress, electrostatic potential, or elastic stress dependent phospholipase C or DG lipase activity on lipid membranes (Figure S2f).…”
Section: Resultsmentioning
confidence: 99%
“…To explore the influence of sorting pressure on the metabolome, we sorted K562 cells under different conditions using either a 70 μm nozzle or 100 μm nozzle on the droplet This could make them more prone to endoplasmic reticulum (ER) stress since NAA sustains the intracellular UDP-Nacetylglucosamine levels, enabling protein synthesis under low glucose conditions, which in turn suppresses endoplasmic reticulum (ER) stress. 28,29 Similarly, several tryptophan metabolism intermediates showed larger changes when sorted with a droplet-based sorter, which are known for their role as antioxidant and ROS scavengers, indicating exposure to oxidative stress. 30 Other metabolites such as nicotinamide, folate, and riboflavin, involved in protecting the cell membrane, proteins, and DNA from oxidative damage, were also significantly reduced in droplet-based cell sorting.…”
Section: Imaging Analysis For Ros Measurementmentioning
confidence: 99%
“…6 [ 39 ], has important roles in the osmoregulation of neuronal cells as well as maintaining nitrogen balance in the brain and energy metabolism in neuronal mitochondria [ 40 , 41 ]. Recently, NAA has also been described as a potent protein aggregation inhibitor [ 42 ]. Lower brain level of NAA has been reported with various neurodegenerative conditions associated with neuronal loss and damage such as PD and Alzheimer's disease using magnetic resonance spectroscopy [ 43 , 44 ].…”
Section: Discussionmentioning
confidence: 99%
“…N-acetylaspartate has been involved in several cellular processes, including osmoregulation in neurons, supplying acetate for myelin lipid synthesis, production of the neuropeptide N-acetylaspartylglutamate, and supporting energy metabolism in neuronal mitochondria [21]. Recent studies have suggested that N-acetylaspartate may have a potential role in stabilizing proteins and inhibiting protein aggregation [51]. Within this context, Gröger and colleagues found significantly decreased N-acetylaspartate concentrations in the substantia nigra of PD patients compared to controls, using three-dimensional magnetic resonance spectroscopic imaging [52].…”
Section: Discussionmentioning
confidence: 99%